Impacts Of Digital Technostress And Digital Technology Self-Efficacy On Intentions To Use Fintech In Indonesia - Santi Putriani; Rika Apriani (Universitas Muhammadiyah Malang, 2022)
The purpose of this study is to see how digital technostress and digital technology self-efficacy (DTSE) affect Generation Z consumers' willingness to adopt FinTech in Indonesia. This study provides knowledge about the impact of technostress and the role of self-efficacy as a moderator on intention to use FinTech. This study uses a questionnaire survey with the criteria of respondents who have used FinTech and Generation Z (born 1993-2012) in Indonesia. A total of 122 respondents were analyzed by Structural Equation Modeling (SEM). The results of the study show that complexity and overload reduce the use of FinTech. In addition, DTSE increases their intention to use FinTech and can reduce the impact of technostress on intention to use FinTech. The results of the research are expected to be input for innovators and policymakers to make FinTech applications easier to use so that consumers will continue to use FinTech to support sustainable development.